Rancang Bangun Mekanisme Peningkat Putaran Bertenaga Sepeda Statis Dengan Keluaran 2700 Rpm Pada Sistem Alternator - Sindu Artha, Gede Andhika; Herwanto, Djoko; Amal Fatkhulloh (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
In engine run practice, it can be simulated by using static bicycle wheel rotation to meet alternator rotation requirements. However, the limitation of human leg muscle to pedalling have not been able to reach the desired rpm. To achieve alternator rotation, design and developable mechanism of rotation is needed. Based on a few identification problems that will be the limitation of problem is how to design developable mechanism of static bike powered with output 2700 rpm. In this design, a knurling wheel with 60 mm of diameter diamond pattern knurling surface as the successor to the 660 mm diameter round bicycle wheel. The chosen gear is a straight gear where the driver gear is 120 mm of pitch diameter, the number of teeth is 60 and the driven gear is 60 mm of pitch diameter with the number of teeth is 30 as successor to knurling wheel. The shaft used is 20 mm of diameter with 7x7 dimention of spie. The bearings used are ball bearing type with bearing number 6004. For the belt and driver pulley, the designer chooses a type A number 35 of v belt with a length of circumference 889 mm belt and 127 mm diameter of driver pulley. The support of gear, driver pulley and alternator used S45C material with 343 N/mm2 of yield strength. From the results of calculations and designs that have been done, the tools are made to work well according to the designer’s criteria. So, this design can be used to help increase the rotation of the bicycle wheel rotation.